Estudo e caracterização de matérias-primas para o desenvolvimento de blocos sílico-calcários - Andrade, Jean Carlos Silva (2009)
The types of products manufactured calcium silicate blocks are very diversified in its characteristics. They include accessory bricks, blocks, products in dense material, with or without reinforcements of hardware, great units in cellular material, and thermal insulating products. The elements calcium silicate are of great use in the prefabricated construction, being formed for dense masses and hardened by autoclaving. This work has for objective develop formulations that make possible the obtaining of calcium silicate blocks with characteristics that correspond the specifications technical, in the State of the Rio Grande of the North, in finality of obtaining technical viability for use in the civil construction. The work studied the availability raw materials from convenient for the production of calcium silicate blocks, and the effect of variations of the productive process on the developed products. The studied raw materials were: the quartz sand from the city of São Gonçalo do Amarante/RN, and two lime, a hydrated lime and a pure lime from the city of Governador Dix-Sept Rosado/RN. The raw materials collected were submitted a testes to particle size distribution, fluorescence of X rays, diffraction of X rays. Then were produced 8 formulations and made body-of-test by uniaxial pressing at 36 MPa, and cured for 7 hours at about 18 kgf/cm2 pressing and temperature of approximately 180 °C. The cure technological properties evaluated were: lineal shrinkage, apparent density, apparent porosity, water absorption, modulus of rupture flexural (3 points), resistance compression, phase analysis (XRD) and micromorphological analysis (SEM). From the results presented the technological properties, was possible say that utilization of hydrated lime becomes more viable its utilization in mass limestone silica, for manufacture of calcium silicate blocks